New Trends in Students’ Reading Habits - Brunilda Zenelaga; Vehbi Miftari; Alma Shehu- Lokaj (Human Research in Rehabilitation, 2024)
The technology era has caused many changes in the reading habits of students, starting in 2011. However, the universities were not prepared for the enormous challenges they faced with the Pandemic, in late 2019 and early 2020. The pandemic has accelerated the habits of students toward digital resources and the use of more and more electronic materials. Facing this phenomenon, accelerated by the effects of Covid-19, the universities have to face the necessity of the adaptation of teaching methods which meant the use of digital materials. The article analyses the change in reading habits and the teaching methods in the Albanian and Kosovan context, showing how the universities in the Republic of Albania and Kosovo have been affected by these changes, embracing approaches to information technology. For this purpose, we have analyzed the changes in reading habits in different public and private universities in Albania and Kosovo. A tested questionnaire has been spread to 672 students in both countries, in different programs and different years of studies. The article shows that under the influence of globalization processes and the development of information technology, reading habits are changing at a frenetic speed, weakening hard copy reading and increasing electronic and that under the Pandemic Covid-19 universities changed the ways of offering teaching methods, accelerating the change of the reading habits of students and weakening the use of printed books as a tool for learning, as well as decreasing the time of reading for pleasure. A more dynamic world caused more focused universities and more rapid changes in the reading habits of the students.